Changes in the landscape of Gediminas Hill’s slopes - Skuodis, Šarūnas; Daugevičius, Mykolas; Dirgėlienė, Neringa; Zakarka, Mindaugas (International Conference “Environmental Engineering”, 2026)
Gediminas Hill has transformed significantly from medieval times to the present. In early history, its slopes were forested and served as a natural defensive barrier. As stone fortifications replaced wooden ones, the slopes were cleared, making the Hill more visible within the growing city. By the Renaissance, artistic depictions showed open, grassy slopes shaped by both nature and human activity. In the 19th century, Romantic artists portrayed the Gediminas Hill as a national symbol, even as erosion began to threaten its stability. Early conservation efforts emerged but were limited in effectiveness. During the Soviet era, landscaping and terracing gave the slopes a more controlled, manicured appearance. Increased tourism and urban development further altered the landscape. In the 21st century, severe erosion and landslides dramatically changed the slopes, exposing their fragility. Recent restoration efforts have reshaped the Hill once again, blending engineering solutions with ecological renewal.